Create Metacognitive Strategies to Unlock Potential - R Rajagopal, Lakshmi (Global journal of Business and Integral Security, 2025)
Human race is very fascinating because of the beautiful mosaic that we are made of. No two human beings are alike – not just in our physical attributes but also due to the differences in the way we think, feel, and behave. We have constantly evolved as a species by pushing the capabilities of human brains beyond the realms of imagination. No algorithm or artificial intelligence, thankfully, as of now can accurately and completely map or predict all of human being’s current feelings or future thinking. For this reason, the study of human brain has been an intriguing topic for researchers over centuries. The fact that each one of us are so unique and that we differ greatly in thinking has been established based on decades of neuroscience research. The act of thinking about one’s own mental processes is called Metacognition, in simpler terms referred as ‘Thinking about Thinking’. Research into Metacognition is a critical one, as it opens a whole new world that we only can imagine exists. The main goals of this study are two-fold: The study helps to create awareness and second and more important one is to create strategies using simple techniques so that Metacognition transcends to a higher order thinking about thinking or Epistemic Cognition. This study accomplishes the above through creation of a ‘Metacognition Maturity Model’ that will help in creating awareness and metacognition strategies at individual level. This model enumerates the various maturity levels that exist in the long yet important journey of creating and improving Metacognition. Understanding Metacognition and moving to an Epistemic Cognition state is a significant step for human race today in light of unprecedented changes being witnessed all around us on multiple fronts. Creating Metacognition strategies gives us the power to thrive in an everchanging and complex world. Doing so, would not only result in metamorphic benefits for the individual at a personal and professional level but also take human race to a totally new level and may decide the sustenance of our race. Key words: ‘Metacognition Maturity Model’, ‘Epistemic Cognition’, ‘Metacognition’, ‘Thinking about Thinking’, Neuroscience, Phenomenology, Cognitive Diversity, Diversity and Inclusion, Cognitive Psychology, Diversity of thinking, Thriving, VUCA world, Fifth industrial revolution